Making America Great Again? National Nostalgia's Effect on Outgroup Perceptions - Behler, Anna Maria C.; Cairo, Athena; Green, Jeffrey D.; Hall, Calvin (Frontiers in Psychology, 2021)
Nostalgia is a fond longing for the past that has been shown to increase feelings of meaning, social connectedness, and self-continuity. Although nostalgia for personal memories provides intra- and interpersonal benefits, there may be negative consequences of group-based nostalgia on the perception and acceptance of others. The presented research examined national nostalgia (a form of collective nostalgia), and its effects on group identification and political attitudes in the United States. In a sample of US voters (N = 252), tendencies to feel personal and national nostalgia are associated with markedly different emotional and attitudinal profiles. Higher levels of national nostalgia predicted both positive attitudes towards President Trump and racial prejudice, though there was no evidence of such relationships with personal nostalgia. National nostalgia most strongly predicted positive attitudes toward president Trump among those high in racial prejudice. Furthermore, nostalgia’s positive relationship with racial prejudice was partially mediated by perceived outgroup threat. Results from this study will help us better understand how the experience of national nostalgia can influence attitudes and motivate political behavior.